2019
DOI: 10.25073/2525-2445/vnufs.4367
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into Students’ Evaluation of and Attitudes Towards Synchronous Computer-Mediated Communication on Language Skills Development in Vietnamese Institutional Context

Abstract: The study explored students’ evaluation of and attitudes towards synchronous computermediated communication (SCMC) on language skills development after a fifteen-week semester ofinstruction, using quantitative and qualitative approach. One class of English level 3 of CEFR – Vietnamesestandard (B1) participated in oral role plays and one class engaged in synchronous online discussions. Theresearch participants filled out the pre- and post- questionnaires and the participants from the SCMC groupwere called for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While some researchers (Chang, Liu, Sung, Lin, Chen & Cheng, 2013;Chen, 2014) claimed that learners' technical prior experience or computer/internet selfefficacy was significantly associated with course satisfaction and confidence, studies by have suggested that computer and internet self-efficacy was not a significant predictor of learners' satisfaction or perceived usefulness of an online course. Other learner-related factors were learners' availability of time, their self-regulated learning, feedback and online presence from peers and instructors Chen, 2014;Mekheimer, 2017, Pham, 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some researchers (Chang, Liu, Sung, Lin, Chen & Cheng, 2013;Chen, 2014) claimed that learners' technical prior experience or computer/internet selfefficacy was significantly associated with course satisfaction and confidence, studies by have suggested that computer and internet self-efficacy was not a significant predictor of learners' satisfaction or perceived usefulness of an online course. Other learner-related factors were learners' availability of time, their self-regulated learning, feedback and online presence from peers and instructors Chen, 2014;Mekheimer, 2017, Pham, 2019.…”
Section: Literature Reviewmentioning
confidence: 99%